2018
DOI: 10.7759/cureus.2612
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Functional Decline in Elderly Female Breast Cancer Patients in Appalachia

Abstract: BackgroundFunctional status has been previously shown in the elderly cancer population to predict both mortality as well as treatment tolerance. The goal of this study was to determine if there are certain subsets of the elderly breast cancer population that are at higher risk of experiencing functional decline following treatment.MethodsPatient charts from the Edwards Comprehensive Cancer Center in Huntington, West Virginia, from January 2006 – January 2016 were reviewed. Relevant inclusion criteria included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Of the residents, 55–60% exhibited functional decline at 1 year post-surgery, with an average drop in MDS-ADL score of 2.8 points following lumpectomy, 4.1 points after mastectomy and 4.6 points post-axillary lymph node dissection (ALND). In support of this, Singh et al [ 5 ] showed that bilateral mastectomies in 314 older Appalachian women aged ≥ 65 years were associated with poorer functional preservation ( p = 0.03) when compared to patients who underwent a unilateral mastectomy or lumpectomy, demonstrating the more apparent decline in FS outcomes after more extensive surgery. A systematic review on the subject [ 6 ], which included 10 studies, further summarised how patients post-ALND experienced appreciable impairment in their autonomy in carrying out their ADLs.…”
Section: Effects Of Breast Cancer Surgery On Functional Status Outcomesmentioning
confidence: 91%
See 4 more Smart Citations
“…Of the residents, 55–60% exhibited functional decline at 1 year post-surgery, with an average drop in MDS-ADL score of 2.8 points following lumpectomy, 4.1 points after mastectomy and 4.6 points post-axillary lymph node dissection (ALND). In support of this, Singh et al [ 5 ] showed that bilateral mastectomies in 314 older Appalachian women aged ≥ 65 years were associated with poorer functional preservation ( p = 0.03) when compared to patients who underwent a unilateral mastectomy or lumpectomy, demonstrating the more apparent decline in FS outcomes after more extensive surgery. A systematic review on the subject [ 6 ], which included 10 studies, further summarised how patients post-ALND experienced appreciable impairment in their autonomy in carrying out their ADLs.…”
Section: Effects Of Breast Cancer Surgery On Functional Status Outcomesmentioning
confidence: 91%
“…Several studies [5][6][7][8][9][10][11] have reported the negative impact of elective cancer treatment on subsequent FS trajectories by examining how it affects the broad areas of ADL and QOL.…”
Section: Effects Of Breast Cancer Surgery On Functional Status Outcomesmentioning
confidence: 99%
See 3 more Smart Citations